2008
DOI: 10.1093/cercor/bhm256
|View full text |Cite
|
Sign up to set email alerts
|

V1 Projection Zone Signals in Human Macular Degeneration Depend on Task, not Stimulus

Abstract: We used functional magnetic resonance imaging to assess abnormal cortical signals in humans with juvenile macular degeneration (JMD). These signals have been interpreted as indicating large-scale cortical reorganization. Subjects viewed a stimulus passively or performed a task; the task was either related or unrelated to the stimulus. During passive viewing, or while performing tasks unrelated to the stimulus, there were large unresponsive V1 regions. These regions included the foveal projection zone, and we r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
202
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(225 citation statements)
references
References 48 publications
(74 reference statements)
18
202
4
Order By: Relevance
“…It is important to note that none of these studies can measure the same neuron at multiple time points, but rather, they must sample from active neurons in similar locations, resulting in potential sampling biases that further complicate their interpretations (2,27). Similar conflicting measurements have been seen in human patients with bilateral foveal lesions from age-related macular degeneration, with some fMRI studies claiming extensive recovery within the V1 SPZ, whereas again, others showed no evidence for reorganization (7,18,35,(43)(44)(45).…”
Section: Comparisons With Studies On the Cortical Effects Of Other Rementioning
confidence: 98%
“…It is important to note that none of these studies can measure the same neuron at multiple time points, but rather, they must sample from active neurons in similar locations, resulting in potential sampling biases that further complicate their interpretations (2,27). Similar conflicting measurements have been seen in human patients with bilateral foveal lesions from age-related macular degeneration, with some fMRI studies claiming extensive recovery within the V1 SPZ, whereas again, others showed no evidence for reorganization (7,18,35,(43)(44)(45).…”
Section: Comparisons With Studies On the Cortical Effects Of Other Rementioning
confidence: 98%
“…Stimulating the occipital cortex of a patient blinded in adulthood by trauma to the optic nerves resulted in abnormal phosphene maps, also suggesting cortical remapping 17 . Despite these reports, the implication that remapping is responsible for the large-scale spread of activation within the lesion projection zone of patients with retinal lesions acquired in adulthood has been seriously questioned [18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies report significant remapping in area V1 of patients suffering from macular degeneration and other retinal lesions (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). The extent of this remapping has recently been called into question, however (1,(13)(14)(15)(16)(17)(18)(19). Less is known about how the visual system remaps to cover the visual field after injury to area V1 or its input projection from the lateral geniculate nucleus (LGN).…”
mentioning
confidence: 99%